A study on an organization awareness towards green office movement among employees in selected private sector department at Petronas Gas Berhad / Fadhilah Syahirah Abdullah Hazawi - Abdullah Hazawi, Fadhilah Syahirah (Faculty Of Business Management, 2016)
The purpose of this study was to identify the organization awareness towards green office movement. The type of this research was descriptive research. This study was conducted at the private sector which in Petronas Gas Berhad. The total respondents that involved in this study were 50 respondents. The instrument used to collect the data was by using questionnaire that consists of four sections which were demographic (Section A), organization awareness (Section B), green office practices (Section C) and 3R concept (Section D). All the data that had been collected were analyzed by using Statistical Package in the Social Sciences Software (SPSS Version 23). The result showed that overall mean for organization awareness were 3.62 in which shows that the respondents have moderate level of organization awareness towards green office movements. Other than that, the overall mean for green office practices were 4.12 in which represented that the respondents were really practice the green office practices in Petronas Gas Berhad. However, the overall mean for 3R concept were 3.76 which mean the respondents had moderately practice the 3R concept in the Petronas Gas Berhad. Therefore, there are several recommendations for practices purpose and future study based on the finding and result of the study. The recommendations for practices at Petronas Gas Berhad were give rewards and recognition to the employees that have practice green office at their workplace which can make them feels that they are being appreciated by the organization and another one is to set up the "green comer" since many employees does not know the benefit of it. Meanwhile, the recommendations for future research were conduct a correlational research, conduct the study at the government sector and last one is focus more on variable.